FISCAL POLICY AS A TOOL FOR SUSTAINABLE DEVELOPMENT IN IRAQ AN ANALYTICAL VISION FOR THE PERIOD (2010-2024) - Dr. Hayder Hussain Ali (Scholar Express Journals, 2025)
The research aims to study the role of fiscal policy
Keywords: fiscal; policy; SUSTAINABLE DEVELOPMENT